Identification and Characterization of Wnt Signaling Pathway in Keloid Pathogenesis - Igota, Shinichi (Ivyspring International Publisher, 2013)
Keloid is characterized by fibroblastic cell proliferation and abundant collagen synthesis. Numerous studies have shown that the Wingless type (Wnt) signaling pathways play key roles in various cellular functions including proliferation, differentiation, survival, apoptosis and migration. The aim of this study was to clarify the role of Wnt signaling pathway in keloid pathogenesis. Primary fibroblast cultures and tissue samples from keloid and normal appearing dermis were used. The expression of Wnt family members, frizzled (FZD)4 receptor, receptor tyrosine kinase-like orphan receptor (ROR)2 and the Wnt signaling downstream targets, glycogen synthase kinase (GSK)3-β and β-catenin were assessed using semi-quantitative RT-PCR, Western blot, or immunohistochemical methods. Of the Wnt family members, Wnt5a mRNA and protein levels were elevated in keloid fibroblasts (KF) as compared to normal fibroblasts (NF). A higher expression of β-catenin protein was also found in KF. No detectable levels of FZD4 receptor and ROR2 proteins were observed in both NF and KF. Functional analysis showed that treatment of NF and KF with recombinant Wnt5a peptide resulted in an increase in protein levels of total β-catenin and phosphorylated β-catenin at Ser33/37/Thr 41 but no significant change in phosphorylated β-catenin at Ser45/Thr 41 positions. In addition, the expression of total GSK3-β protein was not affected but its phosphorylated/inactivated form was increased in NF and KF. Our findings highlight a potential role for a Wnt/β-catenin canonical signaling pathway triggered by Wnt5a in keloid pathogenesis thereby providing a new molecular target for therapeutic modulations.